Ventricular enlargement in new-onset pediatric epilepsies - Jackson, Daren C. (2011)
PURPOSE: To examine baseline and prospective (2-year) changes in third, fourth, and lateral ventricle volumes in children with new-onset idiopathic epilepsies and controls (age 8–18 years). METHODS: Structural magnetic resonance imaging (MRI) were collected from children with idiopathic generalized epilepsy (IGE, n = 29), idiopathic localization-related epilepsy (ILRE, n = 30), and healthy controls (HCs, n = 49). Volumes of the third, fourth, and lateral ventricles were derived and compared across groups, followed by shape analyses, to identify specific regions of ventricular abnormality. Of the initial cohort, a consecutive sample of 71 children returned 2 years later for reimaging and determination of progressive changes in the ventricular system. KEY FINDINGS: At baseline, children with new-onset IGE had significantly larger lateral and third ventricle volumes relative to the HC group. In addition, lateral ventricle enlargement in IGE was significantly greater compared to new-onset ILRE. Shape analysis of the lateral ventricles revealed that volume expansion in IGE was selective for the anterior horn, a region surrounded by the lateral and medial frontal lobes as well as basal ganglia. These abnormalities did not progress over a 2-year interval. SIGNIFICANCE: Abnormalities in brain development prior to onset and diagnosis of epilepsy are evident and reflected in expansion of the ventricular system, especially among children with IGE. These abnormalities appear to represent an antecedent and possibly static finding given the lack of progressive ventricular expansion over the 2-year interval following diagnosis and treatment.